Non-nutritional causes of severe anemia in Kashmiri children - Mir, Naseer Yousuf; Bashir U. Zaman; Wani, Jawad Nazir; Mohammad Imran Malik; Muzaffar Jan; Kaiser Ahmad (International Journal Of Community Medicine And Public Health, 2023)
Background: Anemia is one of the leading causes of mortality and morbidity in children. The etiology of anemia is multifactorial including nutritional anemia, hemolytic anemia, aplastic anemia, storage disorders, hematological malignancies, anemia secondary to some chronic diseases. Methods: The study is an observational study. Physical signs of severe anemia were looked in patients attending outpatient department or admitted in hospital. Children with hemoglobin levels <7 g/dl and in the age group 6 months to 6 years were recruited in study. The aim is to look for non-nutritional etiology of severe anemia in children in Kashmir. Results: Out of 192 children, 97 (50.52%) females and 95 (49.48%) males, with a male, female ratio of around 1:1. A total of 147 (76.56%) children in our study were having nutritional and 45 (23.44%) were having non nutritional causes. Among non-nutritional anemia 30 cases were hemolytic anemia, 11 hypoplastic anemia, 3 leukemia and 1 patient were diagnosed as Osteopetrosis. Conclusions: Though nutritional deficiency anemias are predominant; it may not always be the case. Hemolytic anemia and leukemias should be ruled out while evaluating a patient of severe anemia and pancytopenia. Bone marrow failure syndrome, storage disorders should be ruled out in patients with skeletal anomalies.